Pendampingan Penyampaian SPT Tahunan: Asistensi Kewajiban Pajak Melalui Relawan Pajak - Aribowo, Irwan; Wibowo, Oke; Hadi, Miftahul (Jurnal Ilmiah Pangabdhi, 2024)
Taxpayer compliance and the e-filing mechanism remain challenges in the annual tax return submission. One of the strategies for Tax Awareness Inclusion in Education is the tax volunteer program. PKN STAN actively participates in implementing this tax volunteer program through community service (PkM). The program aims to provide understanding to Taxpayers (TPs) about the procedure for submitting Annual Tax Returns, explain the usage and procedure for validating the Citizenship Identity Number (NIK) to become the Taxpayer Identification Number (NPWP), and assist the Pratama Tax Office of Pondok Aren and the Regional Office of Directorate General of Taxes (DJP) Banten in improving compliance with the submission of Annual Tax Returns and Monthly Tax Returns for Individual Income Tax (PPhOP). PkM activities are conducted through face-to face and online (e-form) methods. The implementation of this Community Service Program received positive responses from the Pratama Tax Office of Pondok Aren and received feedback from the taxpayers at that office. Additionally, this PkM program has successfully identified several issues that can be used as input for improving services at the Pratama Tax Office of Pondok Aren.